Padbagay - Andhika Rahmadhanur; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2021)
This dance work aims to create a dance work which trains and educates a choreographer to become a creative choreographer in preparing ideas through innovative moves as the language in a dance work. The theme in this dance work is about adaptation. The work of this dance is a dramatic dance with a representational symbolic performance. The dance work